Central gene transcriptional regulatory networks shaping monocyte development in bone marrow - Zhang, Zhaoqi; Bossila, Elhusseny A.; Li, Ling; Hu, Songnian; Zhao, Yong (Frontiers in Immunology, 2022)
The development of monocytes in bone marrow is a complex process with multiple steps. We used RNA-seq data to analyze the transcriptome profiles in developing stages of monocytes, including hematopoietic stem cells (HSCs), common myeloid progenitors (CMPs), granulocyte–monocyte progenitors (GMPs), and monocytes. We found that genes related to potassium and other cation transmembrane activities and ion binding were upregulated during the differentiation of HSCs into CMPs. Protein transport and membrane surface functional molecules were significantly upregulated in the GMP stage. The CD42RAC and proteasome pathways are significantly upregulated during the development of HSCs into monocytes. Transcription factors Ank1, Runx2, Hmga2, Klf1, Nfia, and Bmyc were upregulated during the differentiation of HSCs into CMPs; Gfi1 and Hmgn2 were highly expressed during the differentiation of CMPs into GMPs; Seventeen transcription factors including Foxo1, Cdkn2d, Foxo3, Ep300, Pias1, Nfkb1, Creb1, Bcl6, Ppp3cb, Stat5b, Nfatc4, Mef2a, Stat6, Ifnar2, Irf7, Irf5, and Cebpb were identified as potentially involved in the development of GMPs into monocytes in mice and humans. In metabolism pathway regulation, HSCs have high glucose, lipid, and nucleic acid metabolism activities; CMPs mainly up regulate the TCA cycle related genes; and GMPs have extremely active metabolisms, with significantly elevated pentose phosphate pathway, TCA cycle, histidine metabolism, and purine metabolism. In the monocyte phase, the tricarboxylic acid (TCA) cycle is reduced, and the anaerobic glycolysis process becomes dominated. Overall, our studies offer the kinetics and maps of gene transcriptional expressions and cell metabolisms during monocyte development in bone marrow.